EFEKTIVITAS PEMBELAJARAN BERBASIS UNPLUGGED CODING DALAM MENGEMBANGKAN COMPUTATIONAL THINKING SISWA SEKOLAH DASAR : KAJIAN LITERATUR SISTEMATIS BERBASIS PRISMA - Sukma Dwi Meyrena; Tri Joko Raharjo; Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of Unplugged Coding-based learning in developing students’ Computational Thinking (CT) skills at the elementary school level. The research method used is a Systematic Literature Review (SLR) based on the PRISMA protocol by reviewing 13 scientific articles published between 2020 and 2025 from various academic databases such as Google Scholar, SINTA, DOAJ, and ResearchGate. The review explores patterns of Unplugged Coding implementation across different learning contexts and its impact on students’ algorithmic, logical, and problem-solving abilities. The results indicate that Unplugged Coding learning is consistently effective in enhancing students’ computational thinking, creativity, collaboration, and learning motivation. Activities without computers—such as logic games, algorithm simulations, and contextual puzzles—help students grasp CT concepts concretely and enjoyably. Moreover, this approach aligns with the principles of the Merdeka Curriculum by promoting active learning. Therefore, Unplugged Coding serves as an innovative and inclusive learning strategy to improve the quality of elementary education, particularly in schools with limited technological access.